Synergistic effect of ibuprofen with itraconazole and fluconazole against Cryptococcus neoformans - Letícia Fernandes da Rocha; Bruna Pippi; Alexandre Meneghello Fuentefria; Adelina Mezzari (Universidade de São Paulo, 2020)
The present study investigated the association of the non-steroidal anti-inflammatory drug ibuprofen with itraconazole, fluconazole and amphotericin B against Cryptococcus neoformans isolates. The minimal inhibitory concentration (MIC) was found according to M27-A3 protocol and in vitro interactions were evaluated using checkerboard microdilution method. Synergism was demonstrated between azoles and ibuprofen for most isolates. However, no synergistic effects were seen when amphotericin B was combined with ibuprofen. Therefore, our results suggest that ibuprofen presents clinical potential when combined with azole drugs in the treatment of cryptococcosis.